On the volume of terrigenous sedimentation in the Laptev Sea. - Kosheleva, Vera A; Yashin, Dmitry; Musatov, Evgeny E (PANGAEA, 2001)
Volumes of Holocene (10 000 years) terrigenous sediments and annnal sediment supply in the Laptev Sea were evaluated from average thickness of the Holocene veneer. Volumes of deposits supplied from various sediment sourees and by different proeesses (abrasion of hinterland and island shores, river discharge, eolian input, drifting ice) were diseriminating of deposition in the eoastal zone, at river/sea barrier, and in the shelf basin itself. Accumulation by drifting iee and the role of local sea bottom erosion were also considered. Total amount of sediments transported from the Laptev Sea shelf to Amundsen and Nansen Basins of the Aretie Ocean was compared with other Russian Aretie seas.
Tab. 3: Differentiation of eroded material in the Arctic Russian Seas
Keywords: Abrasion; Barents; Barents Sea; Chukchi; Chukchi Sea; East Siberian Sea; E-Siberian_Sea; Kara; Kara Sea; LAP; Laptev Sea